The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1600-0765.1995.tb02136.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of tetracyclines, macrolides, quinolones, clindamycin and metronidazole against periodontopathic bacteria

Abstract: We re-evaluated several antibiotics including newer ones, for their in vitro killing activity, as well as their inhibitory activity, against clinical isolates of periodontopathic bacteria. Tetracyclines were active against Porphyromonas gingivalis, and were highly active against Prevotella intermedia, but demonstrated only a low killing activity against Actinobacillus actinomycetemcomitans. Rokitamycin, a new macrolide, and clindamycin were highly active against P. gingivalis and P. intermedia, but showed very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 15 publications
4
33
0
1
Order By: Relevance
“…The MNCCs of eight test agents were: 0.3 µ m for minocycline, 1 µ m for tetracycline, 3 µ m for ofloxacin and erythromycin, 10 µ m for enoxacin, clarithromycin, and azithromycin, and 100 µ m for roxythromycin. The MIC 90 concentrations of these test agents, except enoxacin, for periodontopathic bacteria, including P. gingivalis , P. intermedia , and A. actinomycetemcomitans , range from 0.031 to 2 µg/ml (0.06–4.0 µ m ) for minocycline, from 0.25 to 4 µg/ml (0.5–8.3 µ m ) for tetracycline, from 0.063 to 1 µg/ml (0.2–2.8 µ m ) for ofloxacin, from 0.125 to 16 µg/ml (0.2–21.8 µ m ) for erythromycin, from 0.125 to 4 µg/ml (0.2–5.3 µ m ) for clarithromycin, from 0.5 to 2.0 µg/ml (0.7–2.7 µ m ) for azithromycin, and from 0.25 to 4 µg/ml (0.3–4.8 µ m ) for roxythromycin (3, 29–31). The results suggest that there would be little or no growth inhibitory effect on basal epithelial cells if ofloxacin, azithromycin, clarithromycin, and roxythromycin were topically administered to the periodontal pocket at the MIC 90 doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNCCs of eight test agents were: 0.3 µ m for minocycline, 1 µ m for tetracycline, 3 µ m for ofloxacin and erythromycin, 10 µ m for enoxacin, clarithromycin, and azithromycin, and 100 µ m for roxythromycin. The MIC 90 concentrations of these test agents, except enoxacin, for periodontopathic bacteria, including P. gingivalis , P. intermedia , and A. actinomycetemcomitans , range from 0.031 to 2 µg/ml (0.06–4.0 µ m ) for minocycline, from 0.25 to 4 µg/ml (0.5–8.3 µ m ) for tetracycline, from 0.063 to 1 µg/ml (0.2–2.8 µ m ) for ofloxacin, from 0.125 to 16 µg/ml (0.2–21.8 µ m ) for erythromycin, from 0.125 to 4 µg/ml (0.2–5.3 µ m ) for clarithromycin, from 0.5 to 2.0 µg/ml (0.7–2.7 µ m ) for azithromycin, and from 0.25 to 4 µg/ml (0.3–4.8 µ m ) for roxythromycin (3, 29–31). The results suggest that there would be little or no growth inhibitory effect on basal epithelial cells if ofloxacin, azithromycin, clarithromycin, and roxythromycin were topically administered to the periodontal pocket at the MIC 90 doses.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum concentrations for the fluoroquinolones were: 10 µ m for tosufloxacin, 30 µ m for sparfloxacin and enoxacin, 100 µ m for lomefloxacin, and 300 µ m for ofloxacin. The MIC 90 , the concentrations required to inhibit the growth of 90% of periodontopathic bacteria, including Porphyromonas gingivalis , Prevotella intermedia , and Actinobacillus actinomycetemcomitans , were 0.06–8 µ m for tetracycline and minocycline and 0.05–5 µ m for tosufloxacin, sparfloxacin, and ofloxacin (3). When extrapolated from the concentration–response curves, the relative survivals of Pel cells exposed to the macrolides at the MIC 90 concentrations were estimated to be: ≥ 53.8% for rokitamycin, ≥ 92.7% for roxithromycin, ≥ 94.6% for clarithromycin, ≥ 97.1% for azithromycin, and ≥ 86.2% for erythromycin (7).…”
mentioning
confidence: 99%
“…Several studies have shown that tetracyclines are active against A. actinomycetemcomitans (15,17,23). Tetracyclines are extensively used as adjuncts in the treatment of periodontitis, a disease affecting the tooth-supporting tissues (gingiva, periodontal ligament, and alveolar bone) and resulting in tooth loss (21,23).…”
mentioning
confidence: 99%
“…originate from anaerobic bacteria, which are particularly sensitive to metronidazole. 21,22 To our knowledge, among the international english literature, metronidazole has yet never been experimented for this procedure. 23,24 Metronidazole is an antibiotic which belongs to the nitro-5-imidazole group.…”
Section: Background and Objectivesmentioning
confidence: 98%